2021
DOI: 10.1108/ijrdm-12-2020-0514
|View full text |Cite
|
Sign up to set email alerts
|

Digital healthcare retail: role of presence in creating patients' experience

Abstract: PurposeThe purpose of this study is to empirically examine the impact of technology-enabled service co-creation on patients' service patronage behaviour in healthcare retailing. The first objective is to examine the mediating roles of spatial presence and co-presence in the relationship between technology enabled co-creation and service experience. The second objective is to investigate if healthcare service experience impacts patients' relationship value with hospitals and subsequent patronage intention.Desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 70 publications
1
10
0
Order By: Relevance
“…However, few studies applied the S-O-R framework to explain the context of telemedicine. For example, Sreejesh et al [ 37 ], in their online healthcare research, demonstrated the technology-enabled co-creation as an incentive option for the users of online medical care consultancy to express their feelings of co-presence, spatial presence, service experience, and positive value perception, which led to patients’ frequent usage behavior. In a similar domain, another study by Chang et al [ 38 ] argued that justice perceptions towards online doctor consultations boost the patients’ trust and satisfaction levels.…”
Section: Theoretical Grounds and Literature Reviewmentioning
confidence: 99%
“…However, few studies applied the S-O-R framework to explain the context of telemedicine. For example, Sreejesh et al [ 37 ], in their online healthcare research, demonstrated the technology-enabled co-creation as an incentive option for the users of online medical care consultancy to express their feelings of co-presence, spatial presence, service experience, and positive value perception, which led to patients’ frequent usage behavior. In a similar domain, another study by Chang et al [ 38 ] argued that justice perceptions towards online doctor consultations boost the patients’ trust and satisfaction levels.…”
Section: Theoretical Grounds and Literature Reviewmentioning
confidence: 99%
“…UTAUT has been widely employed as a theoretical lens to investigate users' intentions and behaviour (Tamilmani et al, 2021;Williams et al, 2015) toward numerous technologies, also in highly interactive scenarios (e.g., Vega et al, 2019), as are the ones involving chatbots. Mogaji et al (2021) found the UTAUT four constructs to explain the use of banking chatbots when conducting a bank transaction, in the same way, Sreejesh et al (2022) use them to enhance patients' experience when using hospital e-service facilitators like chatbots. Kuberkar and Singhal (2020) found the same constructs to influence public transportation chatbot's adoption intention.…”
Section: Utaut and Online Customer Experiencementioning
confidence: 99%
“…Liu et al ( 14 ) proposed an algorithm and used users' purchase data to develop users' diseases to provide product recommendations for pharmaceutical e-commerce platforms. Sreejesh et al ( 15 ) examined how the technology-enabled service co-creation affected patients' service purchase behavior in medical and health services retail. Zehnder et al ( 16 ) studied the growth of Swiss community pharmacies on the internet over the period 2000–2003, which showed that pharmacy-group portals were promoters of internet pharmacies.…”
Section: Introductionmentioning
confidence: 99%